ASSESSING SUSTAINABLE DEVELOPMENT GOALS 1 AND 2 IN SOUTH AFRICAN CONTEXT - Vyas-Doorgapersad S. (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The article summarizes the reasons and objections raised during the scientific debate about SDGs 1 (no poverty) and 2 (zero hunger). The study's primary goal is to investigate the barriers to SDG implementation in the South African setting. Systematisation of the literary sources and approaches for solving the problem indicates that there are several variables that have a detrimental influence on the fight against hunger and poverty. The relevance of this scientific problem decision is important because it highlights the need for the necessary methods to be made available to realize the objectives of the sustainable development agenda. Investigation of the topic SDGs 1 and 2 in the paper is carried out in the following logical sequence: The study methodologies included qualitative methodology, and a literature review was thought to gather pertinent data, which was then analyzed using conceptual analysis. The desktop study, which examined information in a country-specific context, took three months to complete. The research object is the chosen country, South Africa due to its historical reasons for apartheid, which prevented its black people from receiving better education, development, and training possibilities, as well as high-level work positions. Because of the segregation of the majority population's socioeconomic progress, there was a significant racial component to poverty and hunger. The paper presents the results of an empirical analysis that shows that to minimize poverty and food insecurity, several institutional and legal frameworks have been put in place. The research empirically confirms and theoretically proves that; However, nothing has changed; the majority of South Africans are still facing hunger and living below the poverty line. The research results can be useful for policymakers who may utilize the research findings to implement SDGs 1 and 2 for socioeconomic development.